ADVANCED TURBINE WORKING: IMPACT OF WINGLET ON VERTICAL WIND TURBINE DARRIEUS TIPE H - Amir, Ahmad Ihwan; Soenoko, Rudy; Wijayanti, Widya; Setiadhi, David (International Journal of Mechanical Engineering Technologies and Applications, 2024)
In this study, the effect of winglets on improving the performance of type h darrieus wind turbines was investigated. The aim is to determine the most suitable winglet design and find out the magnitude of the increase in wind turbine performance. The method used is experimentation to find the RPM and torque used for calculate the TSR value and turbine power. From all the trial and error experiments, the type of blended winglet that best suited the characteristics of the VAWT. The experimental results show that the addition of blended winglet increases RPM of 13.6% in the 3-blade turbine and turbine it increases of 9% in the 4-blade turbine. The increase in average torque is 13.2% in a 3-blade turbine and 9.4% in a 4-blade turbine. The average increase in power coefficient is 11% in a 3-blade turbine and 9% in a 4-blade blade. In conclusion, the addition of blended winglets produces better torque and power compared to turbine models without winglets.